Hydrogen sulfide as a signal molecule in hematin-induced heat tolerance of tobacco cell suspension - Z.-G. Li; S.-P. Gu (Biologia Plantarum, 2016)
Carbon monoxide (CO) is considered as a new emerging cell signal molecule which is involved in plant growth, development, and acquisition of stress tolerance. In recent years, hydrogen sulfide (H2S) has been found to have similar functions, but crosstalk between CO and H2S in the acquisition of heat tolerance in plants is not clear. In this study, pretreatment of tobacco (Nicotiana tabaccum L.) cells cultured in a suspension with a CO donor hematin significantly increased survival percentage of cells under a heat stress and regrowth ability after the heat stress, alleviated a decrease in cell vitality, and accumulation of malondialdehyde. In addition, treatment with hematin enhanced the activity of L-cysteine desulfhydrase, a key enzyme in H2S biosynthesis, which in turn induced accumulation of endogenous H2S in tobacco cells. Interestingly, hematin-induced heat tolerance was enhanced by addition of NaHS, a H2S donor, but weakened by specific inhibitors of H2S biosynthesis DL-propargylglycine or its scavenger hypotaurine. Furthermore, pretreatment with hemoglobin (a CO scavenger) and zinc protoporphyrin IX (a CO specific synthetic inhibitor) had no significant effect on NaHS-induced heat tolerance of tobacco cells. These results suggest that CO pretreatment could improve the heat tolerance of tobacco suspension cultured cells, and H2S might exert its signal role downstream to CO-induced heat tolerance.